Locus of Control and Job Satisfaction in Australia: The Mediating Role of Job Perception - Tran, Dai Binh (My University, 2021)
This paper investigates the relationship between locus of control and job satisfaction and its domains, using the Household, Income and Labor Dynamics in Australia (HILDA) Survey. Using fixed effects (FE) panel data estimation to control for unobserved individual characteristics, the results first show that internal locus of control is associated with a higher level of overall job satisfaction and other aspects of satisfaction at the workplace. Moreover, the study examines whether perceptions of one's job mediate the association between locus of control and job satisfaction. The findings indicate that internal locus of control correlates with more positive perceptions of aspects of their job, such as a higher level of job security and less stress-related illness, improving job satisfaction. Therefore, this research highlights the role of locus of control in promoting higher job satisfaction, underlining that personality characteristics are a potential asset in the workplace.
Journal of Behavioral and Experimental Economics (formerly The Journal of Socio-Economics)
Keywords: Labour market